Drosophila photoreceptors and signaling mechanisms - Katz, Ben; Minke, Baruch (Frontiers in Cellular Neuroscience, 2009)
Fly eyes have been a useful biological system in which fundamental principles of sensory signaling have been elucidated. The physiological optics of the fly compound eye, which was discovered in the Musca, Calliphora and Drosophila flies, has been widely exploited in pioneering genetic and developmental studies. The detailed photochemical cycle of bistable photopigments has been elucidated in Drosophila using the genetic approach. Studies of Drosophila phototransduction using the genetic approach have led to the discovery of novel proteins crucial to many biological processes. A notable example is the discovery of the INAD scaffold protein, which binds the light activated channel, its activator the PLC and it regulator protein kinase C. An additional protein discovered in the Drosophila eye is the light activated channel Transient Receptor Potential (TRP), the founding member of the diverse and widely spread TRP channel superfamily. The fly eye has thus played a major role in the molecular identification of processes and proteins with prime importance.